Opportunities and challenges to integrate electrochemical storage in central american power grids - Gómez-Ramírez, Gustavo Adolfo (2021)
Stationary systems integration and electric vehicles (in storage conditions) will require actions to improve the existing grid in power electrical systems. To diversify current energy grid and achieve a significant contribution to energies requirements and associated problems due to climate change in Central American region. This article shows main opportunities and challenges in integration, it indicates the evolution and current situation in area. Region presents satisfactory conditions to penetration of several storage technologies with intermittent electricity generation combinations, which it represents a new issue in analysis and studies. Much storage technologies are exposed that but nowadays, they are presented as an opportunity to increase renewable electricity’s production. Therefore, actual technologies must interact with actual grid, storage, intermittent renewable generation, and electrical vehicles. Finally, main opportunities and challenges in storage and electrical vehicles penetration will recognized in power systems analysis.